PEMBANGUNAN SISTEM INFORMASI PENGELOLAAN DONOR DARAH BERBASIS WEB DI PMI KOTA SALATIGA - Andrew Prasetya Kusuma; Nina Setiyawati (Universitas Citra Bangsa, 2026)
PMI Kota Salatiga currently relies entirely on paper forms for various blood donation procedures, making them susceptible to damage and causing inefficiencies in blood donor data recording. This research aims to develop a web-based information system to manage blood donations, specifically the donor registration process and the blood product request process carried out by hospitals. The information system was developed using the Software Development Life Cycle (SDLC) prototyping method with an API-First architecture, utilizing Laravel as the backend, Reactjs as the frontend, and Postgresql as the database. System testing was conducted using User Acceptance Test (UAT), compatibility test, and usability testing with Single Ease Question (SEQ) and System Usability Scale (SUS) methods. The average results of the User Acceptance Test showed an aggregate score of 0.9, while the usability test results yielded an aggregate score of 79.83 for the System Usability Scale and an aggregate of 6.54 for the Single Ease Question. The compatibility testing results demonstrated that the application interface is responsive across various screen sizes. These results indicate that the information system successfully addresses the needs of PMI Kota Salatiga by reducing dependence on physical forms for registration and documentation related to blood donation.